Framework for evaluation of startup promoting policies - Yen, Hoang Thi Hai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
The first section of the paper presents the identification of specific features of startup and the roles of policies in the startup eco-system. As to meet requirements of healthy development of the startup eco-system and objectives of successful startup, the startup related policies should be regularly reviewed and evaluated for appraisal and monitoring of effectiveness of issued policies during implementation stages. The next section of the paper deals with a proposal by the author on a framework for evaluation of startup promoting policies from global concepts to details. The core components of the Framework include: (i) the set of indicators of components for 5 groups: stimulation of creative minds, entrepreneurship, links in startup eco-system down to supports for integration by startups into international markets; (ii) the system of startup related policies needs to be evaluated, from education and training, scientific research, commercialization of research results up to startup culture, incubation, finances and etc.; (iii) the system of concrete measurable indicators such as quantity of incubators, quantity of successfully incubated startups, types of capital sources accessible by startups and etc. The section is finished by two models proposed for brief evaluation of startup promoting policies which may be considered for application in Vietnam. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"> Code: 20020501